Evaluasi Agregat Lokal Sebagai Lapisan Base Perkerasan Permeabel: Evaluation of Local Aggregate as Base Layer of Permeable Pavement - Oktariza, Hendra; Gofar, Nurly (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Permeable pavement is a type of road pavement that allows stormwater to inﬁltrate through the pavement surface and the underlying base layer to reduce surface runoff. Open-graded aggregates are often used as the base layers to temporarily store water and allow the water to infiltrate slowly into the soil below the pavement or through sub-drainage. The strength of open graded material is usually less than the dense-graded materials. Therefore; the mixture of the aggregate for both base and drainage layer need to be designed carefully. In Indonesia, the criteria for aggregate as both base and drainage layer is stipulated in Bina Marga Specification. This study aims at designing an optimum mixture of local aggregate to be used as the base of permeable pavement. The mixture should fulfil the mechanical properties based on laboratory CBR value, and hydraulic properties based on storage capacity and the coefficient of permeability. Five aggregate samples of Andesite origin from South Lampung area were selected for this study. Careful laboratory test procedures were adopted to select configurations of aggregate sizes (design mix formula) that satisfies the requirements both as Aggregate A and as drainage layer. A dense graded aggregate based on the grain size distribution was prepared for design mix formula to meet the requirement as Aggregate A. Then, the fine particles passing No 40 sieve was removed to form open aggregate sample suitable as drainage layer. Both samples were tested for grain size distribution, CBR, permeability and storage capacity. Results show that the local aggregate fulfils the requirements both as base and as drainage layer with average CBR of 92%, average storage capacity of 18.32% and average permeability of 0.05 m/sec. The thickness of the permeable pavement layer could be estimated based on storage capacity and the permeability of the drainage layer.